Anthony of Parma's Quaestio utrum primum principium sive Deus ipse sit potentie infinite: an Introduction and Edition - Côté, Antoine (Université d'Ottawa | University of Ottawa, 2017)
Anthony of a Parma, was an Italian philosopher and medical scholar active in the first three decades of the fourteenth century, whose favorite philosophical authorities were Aristotle and Averroes. He is the author of an intriguing disputed question in which he argues that it is possible to demonstrate that God has infinite power. This article seeks to explicate Anthony’s key arguments in support of this thesis as well as to identify the main contemporary sources behind them. It also highlights the peculiar way in which Anthony attempts to resolve the inconsistency between his position, which ultimately relies on Aristotle and Averroes, and that of the Catholic faith whose truth, he contends, “must in all matters always be put forward,” even though it appears to imply that Aristotle’s position is “totally impossible and false.” The article is followed by the critical edition of the quaestio.
Keywords: infinite power; eternity; Aristotle; Averroes; faith; reason